Metabolic Consequences of Developmental Exposure to Polystyrene Nanoplastics, the Flame Retardant BDE-47 and Their Combination in Zebrafish - Chackal, Raphaël; Eng, Tyler; Rodrigues, Emille M.; Matthews, Sara; Pagé-Lariviére, Florence; Avery-Gomm, Stephanie; Xu, Elvis Genbo; Tufenkji, Nathalie; Hemmer, Eva; Mennigen, Jan A. (Frontiers in Pharmacology, 2022)
Single-use plastic production is higher now than ever before. Much of this plastic is released into aquatic environments, where it is eventually weathered into smaller nanoscale plastics. In addition to potential direct biological effects, nanoplastics may also modulate the biological effects of hydrophobic persistent organic legacy contaminants (POPs) that absorb to their surfaces. In this study, we test the hypothesis that developmental exposure (0-7 dpf) of zebrafish to the emerging contaminant polystyrene (PS) nanoplastics (⌀100 nm; 2.5 or 25 ppb), or to environmental levels of the legacy contaminant and flame retardant 2,2’,4,4’-Tetrabromodiphenyl ether (BDE-47; 10 ppt), disrupt organismal energy metabolism. We also test the hypothesis that co-exposure leads to increased metabolic disruption. The uptake of nanoplastics in developing zebrafish was validated using fluorescence microscopy. To address metabolic consequences at the organismal and molecular level, metabolic phenotyping assays and metabolic gene expression analysis were used. Both PS and BDE-47 affected organismal metabolism alone and in combination. Individually, PS and BDE-47 exposure increased feeding and oxygen consumption rates. PS exposure also elicited complex effects on locomotor behaviour with increased long-distance and decreased short-distance movements. Co-exposure of PS and BDE-47 significantly increased feeding and oxygen consumption rates compared to control and individual compounds alone, suggesting additive or synergistic effects on energy balance, which was further supported by reduced neutral lipid reserves. Conversely, molecular gene expression data pointed to a negative interaction, as co-exposure of high PS generally abolished the induction of gene expression in response to BDE-47. Our results demonstrate that co-exposure to emerging nanoplastic contaminants and legacy contaminants results in cumulative metabolic disruption in early development in a fish model relevant to eco- and human toxicology.